Hubungan Self-Esteem dengan Fear of Missing Out (FoMO) pada Ibu-Ibu di Sumatera Barat - Annisa Rahmi; Yolivia Irna Aviani (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to examine the relationship between self-esteem and fear of missing out (FoMO) among mothers in West Sumatra. FoMO is characterized by anxiety or fear of missing important experiences, especially those seen on social media. A total of 385 mothers aged 18–40 who actively use social media participated in this study. Using a quantitative correlational method and purposive sampling, data were analyzed through Pearson Product-Moment correlation. The results showed a significant negative relationship between self-esteem and FoMO (r = -0.622, p < 0.05). These findings suggest that mothers with lower self-esteem are more prone to FoMO. The study highlights the importance of self-perception in the digital age and provides practical implications for mental well-being among adult women.